Providing Additional Sanctions For Cybercrimes Related To Indecent Crimes - Wahyu Tri Hartanto; Evi Retno Wulan (Fakultas Hukum Dehasen, 2024)
Providing additional sanctions for cyber crimes related to immoral crimes is an important step in dealing with threats that arise in the era of digitalization. This article explores the urgency, types of additional sanctions that may be imposed, judges' considerations in imposing additional sanctions, and the challenges in implementing them. Cyber crimes related to immorality, such as the distribution of pornographic content and grooming, have a serious impact on victims and society. Therefore, providing additional sanctions aims to provide appropriate punishment to the perpetrator and prevent the recurrence of similar criminal acts in the future. Judges need to consider various factors, including the severity of the act, the impact on the victim, and the principles of justice and human rights in determining appropriate additional sanctions. Although faced with a number of challenges, cooperation between various institutions and relevant stakeholders is expected to strengthen law enforcement against cybercrime and provide better protection for society from threats in cyberspace.